Part of it : comics and confessions - Schrag, Ariel (Mariner Books, 2018)
"Ariel Schrag, a critically-acclaimed memoirist and screenwriter, takes us on a painfully funny tour of her awkwardyears, from her childhood in Berkeley to her mid-twenties in Brooklyn, exploring what it means to connect to others when you don't yet know who you are--when you want to be "part of it" but the "it" changes daily. We meet hippie babysitters, mean girls, best friends, former friends, prom dates, girlfriends, sex ed students, and far too many LensCrafters sales associates. These frank, irreverent, and honest comics revelin the uncomfortable--occasionally cringe-inducing--moments from our early years that end up wiring us as people. Part of It furthercements Ariel Schrag as "one of the best pure storytellers...in any medium" (Comics Journal)"--